TINJAUAN MENGENAI SISTEM HIBAH HARTA KEPADA ANAK ANGKAT MENURUT KOMPILASI HUKUM ISLAM - Winda Agustin (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
Abstract Adoption is not a new problem. Since the days of Ignorance, adoption has been done in a way and motivation vary in line with the system and legislation in force at the relevant community. Adoption can be categorized as legal acts due to adopt a child, means someone has taken someone else's child to be a part of his own family and in the end, there will be a legal relationship between the people who raised and raised children. Adopted children have a role as well as proximity to family members adoptive parents, so he sometimes treated the same as their own children. Awarding grants is one way that can be done by foster parents to children adopted as a form of love that has existed between the two. Because Islam clearly confirms that the relationship between the adoptive parents with one child both have adopted do not cause the inheritance relationship heir, thus an adopted child does not inherit from a parent angkatnya.Hibah or testament is one way or effort in terms of transfer of property pursuant -Undang Islam. Grant is the provision of the applicable property during the life of the grantor, while the will is the provision of the applicable property after the death of a will.